A case of panic to pulmonary embolism - Ng, Mansum (BMJ Case Rep, 2015)
Pulmonary embolism (PE) is a rare paediatric diagnosis, but its presence is likely to be underestimated due to the subtle and non-specific nature of its symptoms. Common clinical features of PE include shortness of breath, pleuritic chest pain and acute cardiovascular collapse. Less common symptoms can include persistent unexplained tachycardia, fever or deep vein thrombosis. Rarely do patients present with abdominal pain and self-resolving shortness of breath; symptoms our patient experienced. However, in contrast to popular belief, having normal vital signs does not necessarily lower the probability of PE. D-dimer, a specific fibrin degradation product, has a good negative predictive value for venous thromboembolism diagnosis but its use in children is less clear, with up to 40% of children with PE having a normal D-dimer level. CT pulmonary angiography remains the gold standard in diagnosis.